2016
DOI: 10.1038/srep27935
|View full text |Cite
|
Sign up to set email alerts
|

Dual-color STED microscopy reveals a sandwich structure of Bassoon and Piccolo in active zones of adult and aged mice

Abstract: Presynaptic active zones play a pivotal role as synaptic vesicle release sites for synaptic transmission, but the molecular architecture of active zones in mammalian neuromuscular junctions (NMJs) at sub-diffraction limited resolution remains unknown. Bassoon and Piccolo are active zone specific cytosolic proteins essential for active zone assembly in NMJs, ribbon synapses, and brain synapses. These proteins are thought to colocalize and share some functions at active zones. Here, we report an unexpected findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 67 publications
(146 reference statements)
13
83
0
Order By: Relevance
“…Therefore it is not surprising that I found decreased colocalisation of a number of different presynaptic proteins such as Bassoon, SNAP25 and Syntaxin 1A at mature lamb2 -/-NMJs, where decreased clusters of P/Q-type were found. To further support this, studies have found colocalisation of P/Q-type VGCCs with Bassoon, and these components were distributed in similar pattern Nishimune et al, 2016). In agreement with my findings, others have also shown a decrease in the active zone marker Bassoon at lamb2 -/-NMJs (Nishimune et al, 2004).…”
Section: Failure In Switching Of N-to P/q-type Vgcc Clusters At Matursupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore it is not surprising that I found decreased colocalisation of a number of different presynaptic proteins such as Bassoon, SNAP25 and Syntaxin 1A at mature lamb2 -/-NMJs, where decreased clusters of P/Q-type were found. To further support this, studies have found colocalisation of P/Q-type VGCCs with Bassoon, and these components were distributed in similar pattern Nishimune et al, 2016). In agreement with my findings, others have also shown a decrease in the active zone marker Bassoon at lamb2 -/-NMJs (Nishimune et al, 2004).…”
Section: Failure In Switching Of N-to P/q-type Vgcc Clusters At Matursupporting
confidence: 84%
“…This is further supported with the colocalisation of Bassoon with P/Q-type VGCCs, in which both displayed similar pattern of distribution at the NMJ Nishimune et al, 2016). The direct interaction between active zone components and VGCCs help anchors active zones to the presynaptic membrane (Chen et al, 2011;Chand et al, 2015).…”
Section: Active Zonessupporting
confidence: 53%
See 3 more Smart Citations